LITERATURE REVIEW: THE EFFECT OF SUSTAINABILITY ACCOUNTING ON COMPANY PERFORMANCE - Chotidjah Suhatmi, Erna; Suyatno, Agus; Restiana, Della; Puspita Sari, Desya (LPPM Universitas Duta Bangsa Surakarta, 2023)
The focus of public attention in recent times has been on companies that have gone public. This can be seen from the economic, environmental and social performance provided by the Company. The environment accompanied by social responsibility is able to encourage performance and reduce the company's risks. This research aims to examine in literature the influence of sustainability accounting on the performance of companies listed on the Indonesian Stock Exchange. This research is descriptive research. This research uses secondary methods with a literature review. The data used is research data from several journals that are relevant to the research conducted. Research using the literature review model will discuss or summarize the thoughts obtained from the author's ideas through reviewing several documents on relevant topics. Based on the results of the literature review, it was found that sustainability accounting in the economic disclosure dimension has no influence on the economic performance of a company. The same thing also happens to the environmental disclosure dimension which has no influence on the company's economic performance. In fact, disclosure of social performance has no effect on financial performance. In this case financial performance is represented by return on Assets (ROA). The same thing happens if company performance is replaced with ROS (return on sales), but social disclosure has an effect on company performance as represented by the ROE variable.